Effect of sintering temperatures on microstructural changes and phase transformation of nearly equiatomic microporous NiTi Alloy produced by metal injection moulding / Mashitah Maso’od ... [et al.] - Maso’od, Mashitah; Ismail, Muhammad Hussain; Razali, Rosliza; Subuki, Istiqamah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
In this present work, NiTi alloy were produced by metal injection moulding using elemental powders of Ni and Ti. The binder system comprised of palm stearin (PS). Two compositions of NiTi alloy were investigated; 50 at.% Ni, and 50.8 at.% Ni. Injection moulding was carried at 130°C, followed by solvent extraction using heptane as the solution. In a high vacuum furnace, the samples were thermally debound at 500oC and subsequently sintered at three different temperatures; 1050, 1100 and 1150 °C. All sintered samples were charateried by XRD and SEM for phase and microstructural analysis, respectively. Reversible phase transformation temperatures (PTTs) of austenite to martensite was determined by DSC analysis. The results showed that B2 (Austenite) and B19’ were the main phases identified while minor phases consist of minimal fractions of Ti-rich phases (NiTi2/Ni2Ti4Ox) and Ni- rich phases (Ni3Ti and Ni4Ti3). As composition of Ni content increased, the reversible martensite to austenite PTTs became wider while enthalpy for phase transition decreased. The FESEM microstuctural analysis defined the formation different phases of atomic mass from dissimilar grey scale contrast. Brightest region assumed to be Ni4Ti3 formation and vice versa indicated Ti-rich phases (NiTi2/Ni2Ti4Ox)